Role of the government internal supervisory apparatus and risk management in reducing fraud in Indonesian local governments - Nurul Qamariyyah; Tenripada; Muhammad Ikbal Abdullah; Andi Chairil Furqan (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
Corruption remains a persistent challenge in Indonesia’s local governments, where weak oversight and fragmented controls continue to create opportunities for fraud. This study examines how the capability of the Government Internal Supervisory Apparatus (APIP) and risk management maturity in reducing fraud in Indonesia, using the Corruption Control Effectiveness Index (CCEI) as a proxy. This study employs a quantitative approach, utilizing secondary data from 1,018 observations spanning fiscal years 2021–2022. The analysis employs descriptive statistics, correlation testing, and a fixed effects regression model. The results show that both APIP capability and the risk management index have a significant positive effect on the CCEI. Larger and older local governments tend to perform better, reflecting institutional experience and established control systems. These findings underscore the importance of strengthening APIP capacity and institutionalizing risk management to effectively curb fraudulent practices in Indonesia’s public governance. The study contributes to the literature by integrating APIP capability and risk management effectiveness within a single analytical framework, using the CCEI as a fraud indicator—an approach still relatively rare in research on Indonesia’s local governance.